Membrane Guided Regeneration in Periodontal Tissues - Rajpal, Jaisika; Arora, Aakash; Prasad, Ruchika; Gupta, Madhav Mukund (Journal of Membrane and Separation Technology, 2013)
Periodontal regeneration is the restoration of lost periodontium or supporting tissues and includes the formation of new alveolar bone, new cementum and new periodontal ligament. The concept of GTR is based on the exclusion of gingival connective tissue cells and prevention of epithelial down growth into the wound, thereby allowing cells with regenerative potential (PDL and bone cells) to enter the wound first. GTR consists of placing barriers of different types to cover the bone and periodontal ligament thus temporarily separating them from gingival epithelium. Excluding the epithelium and gingival connective tissue from the root surface during the post-surgical healing phase not only prevent epithelial migration into the wound but also favors repopulation of the area by cells from the periodontal ligament and bone. Purpose and Scope -This review discusses the rationale for using guided tissue regeneration therapy. The review not only attempts to clarify the concept of selective tissue regeneration using non-resorbable and resorbable barriers, but to discuss differences in healing events after treatment with the two types of barriers together with their significance in periodontal therapy. At present, barrier membranes have potential clinical use in promoting periodontal tissue regeneration if patients to be so treated are selected appropriately. Research is still necessary to determine the critical period for guiding the ingrowth of new attachment forming cells and also to further clarify the concept of GTR involving the "wrong cell type" which inhibits periodontal tissue regeneration.